2021
DOI: 10.3389/fpls.2021.653270
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Marker–Trait Associations for Lint Yield Contributing Traits in Upland Cotton (Gossypium hirsutum L.) Using SSRs

Abstract: Improving the yield of lint is the main objective for most of the cotton crop improvement programs throughout the world as it meets the demand of fiber for textile industries. In the current study, 96 genotypes of Gossypium hirsutum were used to find novel simple sequence repeat marker-based associations for lint yield contributing traits by linkage disequilibrium. Extensive phenotyping of 96 genotypes for various agronomic traits was done for two consecutive years (2018 and 2019) in early, normal, and late so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Similar patterns of correlation were reported in previous studies by [3,4,15,22,23,90,[92][93][94][95]. Boll weight showed a negative correlation with NB in all three environments [96]. Likewise, significant, and positive association between BW and NSB is highly beneficial since increase in boll weight will increase the number of seeds per boll, which in turn will result in increased surface area, enhancing the maximum lint percentage.…”
Section: Discussionsupporting
confidence: 87%
“…Similar patterns of correlation were reported in previous studies by [3,4,15,22,23,90,[92][93][94][95]. Boll weight showed a negative correlation with NB in all three environments [96]. Likewise, significant, and positive association between BW and NSB is highly beneficial since increase in boll weight will increase the number of seeds per boll, which in turn will result in increased surface area, enhancing the maximum lint percentage.…”
Section: Discussionsupporting
confidence: 87%
“…A similar correlation pattern has been reported in previous studies [ 79 84 ]. FFN showed a negative correlation with FF [ 7 , 16 , 20 , 24 , 80 ]. Similarly, the significant and positive correlation between No.…”
Section: Discussionmentioning
confidence: 99%
“…Population size has a great impact on association mapping studies, and it has been reported that a relatively large population size ensures sufficient genetic variation, thereby influencing the detection of significant QTLs ( Su et al., 2016 ; Huang et al., 2017 ). Population sizes ranging from 95 to 800 have been previously studied in upland cotton in association studies ( Gapare et al., 2017 ; Sun Z. et al., 2017 ; Dong et al., 2019 ; Kumar et al., 2021 ). Although our population size of 117 released varieties from different agro-climatic zones was not sufficiently large, they are suitable for mapping analysis because they stabilize after many years of genetic recombination ( Nordborg et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%